Assessment of exposure and health risk of mercury in Camp 6, Tuba, Benguet using spatial analysis and decision assistance - Luz, Anna Gabrielle A.; Tan, Irina Y.; Diola, Ma. Brida Lea D.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Small-scale mining activities have been steadily growing in the province Benguet. Because the mine tailings are unregulated, it is discharged straight into bodies of water, specifically Bued River. Small-scale mines utilize mercury to help in the extraction of gold. Mercury from these processes poses danger to human health and may be absorbed via ingestion, dermal contact or inhalation. This study aims to quantify the exposure and risk of mercury of the nearby community in these mining sites which is Camp 6, Tuba, Benguet. Concentrations of mercury in sediments and surface water were determined. Exposure due to ingestion of mercury in drinking water and fish was concluded not critical because their mercury levels were below the detection limit. For sediments, the mercury toxic effect threshold or the maximum acceptable concentration is 1 mg/kg. Results show an average of 0.0813 mg/kg with standard deviation of 0.0945 mg/kg. The values range from 0.013 mg/kg to 0.373 mg/kg. In surface waters, the concentration of mercury ranges from 0.035 ug/L to 1.2425 ug/L, below the DENR Administrative Order No. 34 standard limit which is 2.0 ug/L. The average concentration of mercury in surface water is 0.2023 ug/L with a standard deviation of 0.3563 ug/L. Only dermal contact with and ingestion of both sediments and surface waters were considered in the risk assessment. Exposure assessment shows that the population of Camp 6, Tuba, Benguet is exposed relatively less than US EPA recommended exposure values. Spatial Analysis and Decision Assistance (SADA) software was used for plotting concentration of surface waters and sediments in Camp 6 and the whole of Camp 4. The software also computed for the hazard quotients of the different pathways. A hazard quotient of 0.0096 was obtained for the occupational risk for the total occupational population. A hazard index of 0.1746 was obtained for the recreational risk. They are both less than 1 which is the acceptable hazard index. Results show that the people of Camp 6, Tuba, Benguet are not at risk considering only the dermal contact with and ingestions of sediments and surface waters.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Mercury wastes -- Philippines -- Benguet (Province); Health risk assessment